Penerapan Model Pembelajaran Tipe Jigsaw Untuk Meningkatkan Hasil Belajar Matematika Materi Statistik Pada Siswa Kelas 6 Sd Negeri 9 Maluku Tengah Kecamatan Pulau Haruku - Ode, Rasid; Zurimi, Safarin; Marasabessy, Patma; K, Kasriana; D, Darwin (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study is a Classroom Action Research (CAR) which aims to improve Mathematics learning outcomes in statistics material for grade VI students of SD Negeri 9 Maluku Tengah, Pulau Haruku District through the application of the Jigsaw learning model. The study was conducted in two cycles, with each cycle including the stages of planning, action implementation, observation, and reflection. The results of the study showed a significant increase in student learning outcomes from cycle I to cycle II. In cycle I, the average student learning outcome was 69.02 with a completion rate of 52.95% (9 students completed) and 47.05% (8 students did not complete). In cycle II, the average learning outcome increased to 76.66 with a completion rate of 88.24% (15 students completed) and only 11.76% (4 students did not complete). This increase of 7.64% was influenced by factors such as increased student attendance, activeness in listening to teacher explanations, and focus on understanding the material and solving problems. In addition, student involvement in asking, answering, and expressing opinions creates a more conducive and effective learning atmosphere. Thus, the application of the Jigsaw learning model in this study has proven effective in improving student learning outcomes.